Essential spectra and Drazin invertibility of quasisimilar closed operators - Messirdi, Bekkai; Djellouli, Ghouti; Azzouz, Abdelhalim (My University, 2018)
The purpose of this paper is to introduce several generalizations of the notion of similarity between closed operators on a Hilbert space, in particular, the notion of quasi-similarity and mutually quasi-similarity. Furthermore, we explore to what extend they preserve spectral properties, Drazin invertibility and hyperinvariant subspaces.
Keywords: Similarity; quasi-similarity; mutually quasi-similarity; Fredholm spectrums; Drazin invertibility; hyperinvariant subspaces